Menjejaki Situs Kerajaan Kuna Di Kalimantan (Observasi Lapangan Di Empat Provinsi) - Suwedi Montana (Balai Arkeologi Yogyakarta, 1995)
The question always arises whether the place, port, kingdom that now lives only in its name such as Sampit, Sedu, Katingan, and Kapuhas are the former ancient kingdoms that in the 14th century have long stood and become a kingdom that pays tribute to the Majapahit Kingdom. It is always imagined in the 14th century that these places become the center of politics, the economic center, the cultural center of a country / government that has the freedom to manage its government, has the freedom to establish relations with other countries far away. The shadow became even stronger after listening to the news about the existence of the kingdoms in a written source, 16th-century European written sources still mention these kingdoms.